Impact Of Covid-19 Pandemic: Consumer Buying Behaviour Towards Food Items - et. al., Dr.Sundarameenasenthil, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Consumers are sincerelyapprehensive about the impact of COVID-19, both from a health and economic viewpoint. The publics are replying in a variety of behaviors and have opposingapproaches, behaviors and purchasing habits. The people across the globe are afraid as they endeavor to adapt to a new normal. The COVID-19 pandemic and the lockdown and social distancing directives have disturbed the consumer habits of buying as well as shopping. the consumers are learning to create and learn new habits. The main objectives of the study analyse the consumer buying behaviour of food items. The study contains both primary and secondary data. The primary data composed form consumers through the questionnaire method via Google forms, the sample size is 100. A convenient sampling method was used for the study. The findings of the study Government of India has taken precautionary measures and news media lift the issue of awareness. The consumer buying behaviour absolutely stopped the Covid-19 situation. The international crisis of Covid-19 pandemic has ravaged the world economy and healthcare and uncertainty among billions of people. The buying behaviour features of the coronavirus outbreak. That pandemic situation the social media help to the people and buying behaviour of the food items to stores.